HAMBATAN SOSIAL BUDAYA DALAM PENGARUSUTAMAAN GENDER DI INDONESIA (Socio-Cultural Constraints on Gender Mainstreaming in Indonesia) - ENDANG LESTARI HASTUTI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Women condition in Indonesia on various aspects of life relatively low. Therefore, genderunderstanding to improve women roles, both in the household and in the society is required.This paper aims to observe socio-cultural constraints, both internal and external. Researchresults convinced that women participation in planning and in decision making ondevelopment programs in fact lower than men. Even existing culture in certain communitygive less support and opportunity to women. Women roles between locations differ, similarlyexisting norms in the community. There are many socio-cultural factors that constraintgender mainstreaming. Women participation in the traditional institutions relatively high.Therefore, gender mainstreaming from the central to local government is very much needed.